2021
DOI: 10.1016/j.injury.2021.02.081
|View full text |Cite
|
Sign up to set email alerts
|

The role of shockwaves in the enhancement of bone repair - from basic principles to clinical application

Abstract: Extracorporeal shockwave therapy is a treatment modality, originally introduced into the clinic as lithotripsie, which has also been successfully used in the last two decades in the non-invasive treatment of delayed or non-healing fractures. Initially, the mechanism of action was attributed to microfractureinduced repair, but intensive basic research has now shown that the shockwave generates its effect in tissue via mechanotransduction. Numerous signal transduction pathways have already been demonstrated, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…Besides studying the phenomenon from a molecular point of view, it would also be interesting to evaluate whether nonsurgical options currently in use on Earth to promote and facilitate bone regeneration in patients with healing deficiencies could be applied to space medicine for the treatment of mild fractures, which, in long-term spaceflights, could compromise astronaut performance. Among nonsurgical treatments, we find physical stimulation therapies, such as extracorporeal shockwave treatment (ESWT), low-intensity pulsed ultrasound (LIPUS) or low-level laser therapies (LLLT) [ 99 , 100 , 101 , 102 ]. The advantage of using nonsurgical countermeasures would lie in their non-invasive nature and easy application, which could allow the astronaut, in the event of minor fractures, rapid self-medication.…”
Section: Fractures and Bone Healingmentioning
confidence: 99%
“…Besides studying the phenomenon from a molecular point of view, it would also be interesting to evaluate whether nonsurgical options currently in use on Earth to promote and facilitate bone regeneration in patients with healing deficiencies could be applied to space medicine for the treatment of mild fractures, which, in long-term spaceflights, could compromise astronaut performance. Among nonsurgical treatments, we find physical stimulation therapies, such as extracorporeal shockwave treatment (ESWT), low-intensity pulsed ultrasound (LIPUS) or low-level laser therapies (LLLT) [ 99 , 100 , 101 , 102 ]. The advantage of using nonsurgical countermeasures would lie in their non-invasive nature and easy application, which could allow the astronaut, in the event of minor fractures, rapid self-medication.…”
Section: Fractures and Bone Healingmentioning
confidence: 99%
“…Among non-surgical options, ESWT has emerged as a reliable and effective non-invasive modality for patients with delayed union or non-union [1] . In ESWT, the term EFD is used to indicate the output.…”
Section: Discussionmentioning
confidence: 99%
“…Extracorporeal shock wave therapy (ESWT) is a non-invasive form of treatment that has been developed from extracorporeal shock wave lithotripsy in the field of urology [1] . In 1991, Valchanou et al reported its effectiveness in treating various delayed unions and non-unions for the first time [2] .…”
Section: Introductionmentioning
confidence: 99%
“…A thicker implant, the use of growth factors (such as bone morphogenic proteins) or early extracorporeal shock wave therapy, and a more restrictive postoperative rehabilitation protocol might avoid implant failure. Mittermayr et al [18] reported in a recent study that extracorporeal shock wave therapy is a reliable, safe, and highly effective treatment for delayed union and nonunion. Moreover, Wehner et al [19] showed that for tibial shaft fractures the diameter of intramedullary nails should be as large as possible and the annular gap should be minimized to avoid a prolonged healing time.…”
Section: Discussionmentioning
confidence: 99%